Phenotypic stability for grain equivalent in dual-purpose sorghum (Sorghum bi-color) - KUMAR, M HEMANTH; REDDY, T YELLAMANDA; SRIEENIVAS, B (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during kharif season of 1991-93 to pickup dual purpose (grain and fodder) sorghum(Sorghum bicolor' (L.) Moench) varieties suitable to low rainfall Alfisols. Twenty one sorghum genotypes were grownin 3 years at Anantapur representing scarce rainfall area. Grain equivalent was considered as better index than grain orfodder or biomass yield for identifying the best dual-purpose variety. Based on stability parameters 'SPV 669' and 'IS6962' sorghum were found to be the best dual-purpose varieties suitable for unfavourable environmental conditions.Based on mean values 'AJ 140', 'SPV 946' and 'SPV 819' may also be considered for recommendation to the scarcerainfall areas.